Komparasi Antara Konsep Moderasi Beragama Dalam Al-Qur’an Dengan Teologi Wahdatul Wujud Serta Filsafat Perenialism - Muhammad Zamroji; Ria Puspitasari (LPPM IAI Hasanuddin Pare-Kediri, 2025)
Maintaining a balance between religious rights and national commitment is a challenge for every Indonesian citizen. Therefore, religious moderation is an urgent means to realize the benefits of a harmonious, peaceful and tolerant religious and national life. The similarities in context regarding the concept of religious moderation in the Qur'an and the perspectives of wahdatul wujud theology and perennialism philosophy, which have differences and similarities in concept, form the basis of this study, leading the author to conduct a comparative analysis. This study aims to describe the idea of religious moderation as a basis for logical thinking and understanding religion in a universal, profound, and systematic manner. The objectives of this article are (1) to understand the concept of religious moderation from the perspective of the Qur'an and the perspectives of wahdatul wujud theology and perennialism philosophy, and (2) to compare the concept of religious moderation in the Qur'an and the perspectives of wahdatul wujud theology and perennialism philosophy. This study uses a library research method with comparative analysis techniques. The results of the study show that, basically, there are similarities and differences in the principles of constructing the values of religious moderation in the views of the Qur'an, Wahdatul Wujud theology and perennialism philosophy, which teach humans the importance of humanism, harmony (tolerance), appreciation and respect for others, national commitment, anti-violence, and accommodating local cultures. This is the meaning of religious moderation as part of the protection of religion (hifzh ad-dîn).